Prediction of stroke recurrence for patients with middle cerebral artery atherosclerotic disease by CT perfusion - Zhang, Xi; Li, Zhi; Zhang, He; Chen, Zhibin; Duan, Guangxin; Huang, Shi; Shi, Hongchao; Zhang, Yunfeng; Du, Junhao; Xiao, Guodong; Luo, Yun (Frontiers in Neurology, 2026)
BackgroundThis paper aimed to test the feasibility of computed tomography perfusion (CTP) in predicting stroke recurrence in patients with symptomatic middle cerebral artery atherosclerotic disease.MethodsThis is a retrospective study. 322 patients from 4 advanced stroke centers diagnosed as symptomatic middle cerebral artery atherosclerotic disease, including severe stenosis and occlusion were recruited. All patients underwent head CTP, digital subtraction angiography (DSA), MR 14-21 days after onset. Stroke recurrence of patients within 3 months was recorded. Patients were divided into recurrence group and control group according to whether stroke recurrence 3 months after onset. The association of imaging characteristics, other risk factors and patients stroke recurrence was assessed.Results104 patients presented stroke recurrence within 3 months after onset. Patients in recurrence group showed more severe vascular stenosis (p < 0.001) and presented with larger hypoperfusion area than control group, as shown by larger Tmax>4 s, Tmax>6 s, Tmax>8 s, Tmax>10s volume (p < 0.001). The multiple logistic regression showed that the volume of Tmax>4 s (OR = 1.061 per 10 mL increase, 95% CI: 1.005–1.122, p = 0.033) and Tmax>6 s (OR = 1.265 per 10 mL increase, 95% CI: 1.093–1.483, p = 0.002) at 14–21 days after stroke were strongly associated with stroke recurrence, Tmax>4 s (AUC = 0.76, 95% CI: 0.70 to 0.81, p < 0.001) and Tmax>6 s (AUC = 0.74, 95% CI: 0.68 to 0.81, p < 0.001) volume had a high discriminative ability for a poor outcome. Tmax>4 s volume larger than 133.60 mL being an optimal cutoff (sensitivity = 80.7% and specificity = 58.6%, Youden index = 39.3%) and Tmax>6 s volume larger than 17.95 mL being an optimal cutoff (sensitivity = 83.5% and specificity = 58.7%, Youden index = 42.2%).ConclusionSymptomatic middle cerebral artery atherosclerotic stenosis or occlusion patients with severe hypoperfusion might suffer a higher risk of stroke recurrence. Volume of Tmax>4 s and Tmax>6 s in CTP could be used to predict the prognosis of these patients.